Creating, Providing, and Performing Space - Viega, Michael (Voices: A World Forum for Music Therapy, 2017)
This special edition of Voices: A World Forum for Music Therapy is dedicated to the glorious blurred boundaries of art, research, and performance. There is an array of traditional scholarship, aesthetic texts, digital media projects, critical self-reflection, cultural exploration, and social critique. I have experienced pain, joy, connection, disconnection, longing, sadness, anger, and beauty within all of the work presented here. As you engage these works of art, you may experience some of the same feelings, or you might walk away with completely different perceptions. It is our collective and collaborative heuristic experience with the artwork contained herein that will shine a spectrum of color onto the complex and daunting social issues addressed by these artists, scholars, researchers, and wonderful human beings.